Penggunaan Media Gambar Untuk Meningkatkan Kemampuan Berbicara Anak Di Taman Kanak-Kanak (TK) Dharma Bunda Pekanbaru - Raja Agustina (Pusat Pengembangan Ilmiah dan Penelitian Mahasiswa Universitas Negeri Padang, 2014)
The use of imprecise media in teaching and learning process had caused some problems in achieving students learning mastery. The process of teaching and learning were focused on the teachers that the students could not develop their own ideas. Related to the problems which were found in the field, the researcher tried to find the solution by applying pictures as a media in teaching and learning process. This research was aimed to see how much pictures can improve students speaking ability in Dharma Bunda Kindergarten Pekanbaru. It was hypothesized that the use of pictures in teaching and learning process can improve students speaking ability. This was a classroom action research which was conducted in Dharma Bunda Kindergarten Pekanbaru at second semester in 2008/2009 of academic year. The data was collected by administering a test and also used observation sheet for students and teachers activities. Then the data was analyzed by using quantitative approach. The result of data analysis showed that the use of pictures can improve students speaking ability in Dharma Kindergarten Bunda Pekanbaru especially for those who were registered in 2008/2009 of academic year. The implication of this research was the use of pictures can improve students activity as well as their speaking ability.